Web Presensi Berbasis Progressive Web App (PWA) Menggunakan Laravel dan MySQL - Rosal Haris Madani; Suhanda Saputra (Journal of Research and Publication Innovation, 2024)
The use of websites in the world of education can not only be used as a tool in the teaching and learning process but can also be used as an administrative tool in the field of employee attendance. Depok National Vocational School which is one of the Vocational High Schools in Depok City which in the employee attendance process still uses a manual system by using initials or by having a picket teacher. This is not implemented effectively because recording or reporting attendance can lead to fraud such as forged signatures and different arrival times so that inaccurate attendance data will affect the calculation of salary payments. And also when employees are unable to attend, they have to give permission personally to the relevant parties and this will create confusion later when recording attendance data because the data is separate from the attendance data signed at school, and also the risk of losing the permission data is greater. If allowed to continue, it will endanger the company's budget and reduce the level of discipline and reduce employee performance. Therefore, a Progressive Web App (PWA) based attendance system website was created which aims to make it easier for the academic community to carry out administrative processes such as attendance.